Hydrogen sulfide induces Ca2+ release from intracellular Ca2+ stores and stimulates lactate production in spinal cord astrocytes. (October 2021) - Nii, Takeshi; Eguchi, Ryota; Otsuguro, Ken-ichi
Highlights: H2 S induces intracellular Ca 2+ response by inhibiting mitochondrial respiration. H2 S releases Ca 2+ from the endoplasmic reticulum through the translocon complex. H2 S-mediated Ca 2+ release stimulates compensatory glycolysis and lactate release. Abstract: Hydrogen sulfide (H2 S) is a well-known inhibitor of the mitochondrial electron transport chain (ETC). H2 S also increases intracellular Ca 2+ levels in astrocytes, which are glial cells and that supply lactate as an energy substrate to neurons. Here, we examined the relationship between H2 S-induced metabolic changes and Ca 2+ responses in spinal cord astrocytes. Na2 S (150 μM), an H2 S donor, increased the intracellular Ca 2+ concentration, which was inhibited by an ETC inhibitor and an uncoupler of mitochondrial oxidative phosphorylation. Na2 S also increased the accumulation of extracellular lactate. Na2 S alone did not change intracellular ATP content, but decreased it when glycolysis was inhibited. The Na2 S-induced Ca 2+ increase and accumulation of extracellular lactate were inhibited by emetine, an inhibitor of translocon complex, which mediates Ca 2+ leak from the endoplasmic reticulum (ER). Furthermore, an inhibitor of the Ca 2+ -sensitive NADH shuttle decreased Na2 S-mediated accumulation of lactate. We conclude that inhibition of the mitochondrial ETC by H2 S induces Ca 2+ release from mitochondria and the ER in spinal cord astrocytes, which increases lactate production. H2 S may promote glycolysis by activating the Ca 2+ -sensitive NADH shuttle and facilitating the supply of lactate from astrocytes to neurons.